1987
DOI: 10.1007/bf01296133
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of indirect methods of estimating small bowel transit in man

Abstract: Experiments were carried out in healthy volunteers to explore the utility of a new [14C]lactulose breath test for measuring small intestinal transit time in man and to use this procedure to test whether two antidiarrheal agents, codeine and clonidine, alter small intestinal transit time during digestion of a liquid meal. In an initial validation study performed in 12 subjects (three studies in each subject), a liquid test meal containing 10 g [14C]lactulose was administered and the colonic entry time estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Under these conditions, OCTTs differed between 70 and 205 min (Heine, Mohr and Münch, 1996;Wutzke et al, 1996). Other conventional methods for evaluation of OCTTs are based on radiographic and scintigraphic methods using barium meals, 111 In-labelled plastic particles, [ 14 C]xylose, [ 14 C]lactulose and [ 99m Tc]DTPA (Barrow et al, 1992;Ghoos et al, 1993;Hirakawa et al, 1988;King and Toskes, 1986;Madsen et al, 1991;Pressman et al, 1987;Sciarretta et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, OCTTs differed between 70 and 205 min (Heine, Mohr and Münch, 1996;Wutzke et al, 1996). Other conventional methods for evaluation of OCTTs are based on radiographic and scintigraphic methods using barium meals, 111 In-labelled plastic particles, [ 14 C]xylose, [ 14 C]lactulose and [ 99m Tc]DTPA (Barrow et al, 1992;Ghoos et al, 1993;Hirakawa et al, 1988;King and Toskes, 1986;Madsen et al, 1991;Pressman et al, 1987;Sciarretta et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Other conventional methods for the determination of OCTT are based on radiographic and scintigraphic methods using 111 In-labelled plastic particles, [ 14 Barrow et al, 1992;Hirakawa et al, 1988;Madsen et al, 1991;Pressman et al, 1987;Sciarretta et al, 1994). For ethical reasons, invasive or radioactive methods for OCTTmeasurements are not justificable, especially in childhood and pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such a drawback, a solid food has been substituted for a liquid meal with apparent excellent results, achieving coefficients of variation, below 10%, for repeated determinations [18,35,36] and improving the reproducibility obtained with lactulose diluted in water [10,18]. Other investigators, however, have not observed such improvement [28], and at least one study obtained a high coefficient of variation of 17% with a liquid meal substrate [37]. In the present study, when lactulose was administered in a liquid formula meal the reproducibility of the test was unchanged relative to lactulose in water as substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The SMD indicated an increase in transit time, however this was nonsignificant (SMD = 0.31, 95% CI −0.17 to 0.79; I 2 = 53%; see Supplementary Figure 14). The WMD was also calculated: clonidine increased significantly orocaecal transit time by 0.52 hours (31.2 minutes; 95% CI 0.06−0.98 h; I 2 = 61%) [Baxter et al 1987;Pressman et al 1987;Baumer et al 1989;Rubinoff et al 1989;Morali et al 1991;Mann and Shinkle, 1998;Camilleri et al 2003] (Supplementary Figure 15). Furthermore, clonidine decreased rectal losses of sodium (SMD = −0.81, 95% CI −1.67 to 0.05; I 2 = 59%; see Supplementary Figure 16) [Schiller et al 1985;Rabbani et al 1989;Buchman et al 2006] and chloride (SMD = −0.75, 95% CI −1.34 to 0.16; I 2 = 0%) (Supplementary Figure 17) [Schiller et al 1985;Rabbani et al 1989], but did not affect bicarbonate (SMD = 0.29, 95% CI −0.63 to 1.21; I 2 = 53%; see Supplementary Figure 18) and potassium losses (SMD = 0.11, 95% CI −0.46 to 0.67; I 2 = 0%; see Supplementary Figure 19) [Schiller et al 1985;Rabbani et al 1989] while it did not affect absorption of sodium (SMD = 0.31, 95% CI −0.44 to 1.06; I 2 = 0%; see Supplementary Figure 20) and potassium (SMD = 0.20, 95% CI −0.55 to 0.94; I 2 = 0%; see Supplementary Figure 21) [Schiller et al 1985;Buchman et al 2006].…”
Section: Meta-analysis Of the Main Outcomementioning
confidence: 99%
“…The case reports [Mcarthur et al 1982;Sacerdote, 1986;Zimmermann et al 1986;Roof, 1987;Migliore et al 1988;Scholz et al 1991;Schworer et al 1995] are discussed narratively in a separate section below because of possible high placebo rates and are not included in the meta-analysis. The remaining 24 trials/case series included 10 studies with healthy volunteers (total sample size = 150 participants) [Schiller et al 1985;Baxter et al 1987;Pressman et al 1987;Baumer et al 1989;Gregersen et al 1989;Rubinoff et al 1989;Thollander et al 1997Thollander et al , 1999Mann and Shinkle, 1998;Viramontes et al 2001] and 14 studies (total sample size = 493 patients) with faecal incontinence, irritable bowel syndrome, diabetes, alcohol withdrawal, heroin withdrawal, ultra-rapid opioid detoxification, short bowel syndrome (high output ileostomy or high rectal output), intestinal transplant and cholera patients [Fedorak et al 1985;Bretzke, 1987;Gupta and Jha, 1988;Rabbani et al 1989;Baumgartner and Rowen, 1991;Morali et al 1991;Rovera et al 1997;Camilleri et al 2003Camilleri et al , 2009Mcdoniel et al 2004;Buchman et al 2006;Farzam and Najafi, 2009;Bharucha et al 2010Bharucha et al , 2014. Results regarding statistical analysis of these studies are described in the following.…”
Section: Systematic Review and Meta-analysis Of Trialsmentioning
confidence: 99%